Translation and Cultural Adaptation of the Modified Child Dental Anxiety Scale - Faces (MCDASf) into Brazilian Portuguese - Taís de Souza Barbosa; Marina Sousa Azevedo; Giovanna Lucas Vidal; Paulo Veríssimo Barbosa D'Almeida; Carolina Dea Bruzamolin; Luciane Rezende Costa; Vanessa Polina Pereira da Costa; Marília Leão Goettems (Association of Support to Oral Health Research (APESB), 2022)
Objective: To translate and culturally adapt the Modified Child Dental Anxiety Scale - Faces (MCDASf) into Brazilian Portuguese. Material and Methods: The MCDASf consists of eight questions about anxiety toward dental procedures that are answered on a five-point Likert scale ranging from "not worried" (1 point) to "very worried" (5 points). The answers correspond to a scale of face drawings ranging from extremely negative to extremely positive. The process consisted of initial translation, back-translation, expert committee review, and pretesting. Results: The first revised version was applied to 32 children aged 5 to 12 years, 16 from the city of Governador Valadares, Brazil (southeastern region) and 16 from the city of Pelotas, Brazil (southern region). In the first pretest, Item 5 was misunderstood by 6.25% of children in the southern region; Item 6 by 6.25% in both regions; Items 7 and 8 by 87.5% and 100% of those from the southeastern region, respectively, and by 12.5% and 25% of those from the southern region, respectively. Items 7 and 8 were modified by the expert committee, and the second revised version was applied to 32 children, 16 from each region. The only misunderstood items were 4 and 5, both by a 7-year-old boy in Governador Valadares. Conclusion: The Brazilian Portuguese version of the MCDASf was well understood by the sample of children.